A word on netting of angiotensin-converting enzyme inhibitor therapy in hypoplastic left heart syndrome following stage-I. (28th August 2021) - Schranz, Dietmar; Krasemann, Thomas
Abstract: NPC-QIC Registry data showed that angiotensin-converting enzyme inhibitors were described in almost 38% for patients with single ventricle physiology after stage-I Norwood palliation. However, mortality and ventricular dysfunction or atrioventricular valve insufficiency seems to be not improved by oral application of angiotensin-converting enzyme inhibitors. The final conclusion was that despite limited evidence of benefit for patients with hypoplastic left heart syndrome, prescription of angiotensin-converting enzyme inhibitors during interstage is still common. Taking into account of the predominant cardiovascular regulation in newborns and young infants by circulating catecholamines, no real improvement is to be expected from angiotensin-converting enzyme inhibitor monotherapy. The goals of drug therapy after stage-I Norwood palliation in hypoplastic left heart syndrome are prevention of systemic right ventricle failure, balancing pulmonary and systemic blood flow, and reduction of oxygen consumption with regard to limitations of oxygen supply by the single ventricle, furthermore, avoiding harmful effects of endogenous catecholamine production in the long term on somatic and cognitive development. In this light of knowledge, we want to recommend the use of a long-acting and highly specific ß1-adrenoreceptor blocker for almost all patients after stage-I Norwood palliation and a combination with angiotensin-converting enzyme inhibitors only by indication after exclusion of potential side effects.